Lung ultrasonography score as a predictor of RDS severity in premature infants - Romadhan, Meddy; Etika, Risa; Utomo, Martono Tri; Angelika, Dina; Handayani, Kartika Darma; Ayuningtyas, Wurry; Violetta, Lenny (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: This study aimed to analyze lung ultrasound (USG) scores as a predictor of Respiratory Distress Syndrome (RDS) severity in premature infants. The research was conducted using an observational analytic method with a cross-sectional approach on 51 premature infants treated in the NICU at Dr. Soetomo Hospital, Surabaya.Methods: Data collection was performed by measuring lung USG scores at 0-3 hours and 12-24 hours after birth and analyzing the relationship between these scores and the severity of RDS based on chest X-rays, Downes Score, and Oxygen Saturation Index (OSI).Results: The study showed a significant positive correlation between lung USG scores at 12-24 hours and RDS severity based on chest X-rays (r=0.307, p=0.029). Additionally, there was a significant relationship between lung USG scores at 12-24 hours and Downes Score (r=0.355, p=0.011), while lung USG scores at 0-3 hours had a positive correlation with OSI (r=0.483, p=0.049).Conclusions: This study demonstrated that lung USG scores can be used as a predictor of RDS severity in premature infants, supporting the potential of lung USG as a non-invasive and effective method for early RDS assessment, which may assist in guiding clinical decisions related to surfactant administration and other interventions.